2014
DOI: 10.1007/s11262-014-1114-4
|View full text |Cite
|
Sign up to set email alerts
|

miR-27a suppresses EV71 replication by directly targeting EGFR

Abstract: Enterovirus 71 (EV71), a major causative agent of hand, foot, and mouth disease, has broken out several times and was accompanied by neurological disease. microRNAs, a class of small non-coding RNAs that are approximately 20 nucleotides long, play important roles in the regulation of various biological processes, including antiviral defense. However, the roles of miRNAs in EV71 replication and pathogenesis are not well understood. In this study, we found that the expression of miR-27a was significantly decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 23 publications
0
26
0
Order By: Relevance
“…The upregulated miR-363 is also known to induce apoptosis (Zhang et al, 2014; Zhou et al, 2014; Hu et al, 2015; Li et al, 2015). The upregulation of miR-21-3p and miR-363 in PPRV infections suggests synergistic effect of these miRs along with the virus in inducing apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The upregulated miR-363 is also known to induce apoptosis (Zhang et al, 2014; Zhou et al, 2014; Hu et al, 2015; Li et al, 2015). The upregulation of miR-21-3p and miR-363 in PPRV infections suggests synergistic effect of these miRs along with the virus in inducing apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…According to current and our previous studies, rhabdomyosarcoma (RD) cells and the Henrietta Lacks strain of cancer (HeLa) cells can be used as in vitro models to investigate the interplay between EV71 and its host [16, 27ā€“29]. To determine whether hsa-let-7c-5p is involved in EV71 infection, we first examined the expression of mature hsa-let-7c-5p in uninfected and EV71-infected RD cells by stem-loop quantitative reverse transcription polymerase chain reaction (qRT-PCR).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we have found that miR-27a expression is downregulated and that hsa-let-7c-5p expression is upregulated in RD cells during EV71 infection. Further, we have reported that miR-27a overexpression suppresses viral replication through the regulation of EGFR-mediated pathways [16]. It is of interest to investigate the role of hsa-let-7c-5p miRNA upregulation in EV71 infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oligonucleotides: Previous reports have described the antiviral effects of RNA-based therapeutics, such as siRNA,shRNA and miRNA, targeting the VP1, 3D, 2C genes, or the 3' UTR of the HEV71 genome, resulting in antiviral activity [121][122][123][124][125][126][127][128] . However, whilst plasmid-derived shRNAs are widely used for laboratory studies, they are not suitable for antiviral therapy.…”
Section: Interferonsmentioning
confidence: 99%